Pengembangan Objek Wisata Pelabuhan Jayanti Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Sekitar - Sri Wulan Purnamasari; Dadang Kuswana (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
This study aims to determine (1) The government’s strategy in managing Jayanti Port Attractions in attracting tourists. (3) Implementation of the Development of Jayanti Port Tourism Objects for the economic welfare of the surrounding community. (3) Results of the development of Jayanti Port Torism Object for the economic welfare of the surrounding community. The method used in this study is descriptive method with a qualititative approach to solve the problem being examined by describing the actual resultas of the object of research. The results of this study indicate that the government in implementing the development of Jayanti Port Tourism Objects has made various efforts, although not yet maximally. The implementation of the development of tourism objects is said to have been successfully seen from several welfare indicators such as improvements in meeting basic needs, family education, health, and housing. Development of Jayanti Port Tourism Objects is able to create employment oppurtinities, both in the main sector tourism support.